Recent Approaches and Success of Liposome-Based Nano Drug Carriers for the Treatment of Brain Tumor - Shaw, Tapan K.; Paul, Paramita (Current Drug Delivery, 2022)
Brain tumors are nothing but a collection of neoplasms that originate either from areas within the brain or from systemic metastasized tumors of other organs spread to the brain. It is a leading cause of death worldwide. The presence of the blood-brain barrier (BBB), blood-brain tumor barrier (BBTB), and some other factors may limit the entry of many potential therapeutics into the brain tissues in the tumor area at the therapeutic concentration required for satisfying effectiveness. Liposomes play an active role in delivering many drugs through BBB into the tumor due to their nanosize and physiological compatibility. The surface of the liposomes can be modified with various ligands that are very specific to the numerous receptors overexpressed onto the BBB as well as onto the diseased tumor surface site (i.e., BBTB) to deliver selective drugs into the tumor site. Further, this colloidal carrier can encapsulate both lipophilic and hydrophilic drugs due to its unique structure. Moreover, the enhanced permeability and retention (EPR) effect can be an added advantage for nanosize liposomes to concentrate into the tumor microenvironment through relatively leaky vasculature of solid tumor in the brain where no penetration restriction applies compared to normal BBB. Here in this review, we have tried to compile the recent advancement along with the associated challenges of liposomes containing different anti-cancer chemotherapeutics across the BBB/BBTB for the treatment of gliomas that will be very helpful for the readers for better understanding of different trends of brain tumor targeted liposomes-based drug delivery and for pursuing fruitful research on the similar research domain.
Keywords: enhanced permeability and retention effect